Development and validation of subscales to assess perceived support for self-management of mood or emotional problems: Results from a randomized trial. Issue 12 (December 2017) - McCusker, Jane; Haggerty, Jeannie; De Raad, Manon; Belzile, Eric; Bouharaoui, Fatima; Beaulieu, Christine; Yaffe, Mark; Ciampi, Antonio
Highlights: Two new subscales assess perceived self-management support for mood problems. Both subscales evidenced high reliability and good concurrent convergent validity. Both subscales were sensitive to a depression self-care coaching intervention. One subscale was sensitive to depression treatment given outside the trial. Equivalent generic measures were not sensitive to mental health interventions. Abstract: Objectives: To validate 2 new patient-reported measures of self-management support from health professionals for mood and emotional problems. Methods: The sample comprised primary care patients with chronic physical conditions and co-morbid depressive symptoms enrolled in a randomized trial of telephone coaching of a depression self-care intervention (n = 120). At 6-month follow-up, patients completed 2 subscales with respect to support for self-management of their chronic physical condition(s): 1) Self-Management Information (SMInfo-Phys); and 2) Care Plan (CP-Phys) and equivalent subscales adapted to assess self-management support for mood and emotional problems: SMInfo-Mood and CP-Mood. Subscale scoring was assessed with Item Response Theory (IRT) analysis. Convergent validity of the mood subscales was assessed. The sensitivity of the mood and physical condition subscales to mental health interventions was assessed with generalized estimating equations (GEE). Results: The mood subscales were associated with relevant measures of perceived unmet mental health needs. Both SMInfo-Mood and CP-Mood were sensitive to the coaching intervention; CP-Mood was also sensitive to receipt of depression treatment outside the trial. Conclusion: This study provides preliminary evidence for the validity of the 2 new subscales. Practice implications: The subscales may be used to assess perceived health professional support for self-management of mood and emotional problems.